Crohn's Disease of the Esophagus: Three Cases and a Literature Review - Ivan Rudolph; Franz Goldstein; Anthony J DiMarino (Canadian Journal of Gastroenterology)
Three cases of esophageal Crohn's disease (CD) are described, each with dysphagia and/or odynophagia caused by esophageal ulceration. All three patients had associated ileocolitis. One patient followed for a prolonged period responded to treatment with sulfasalazine and prednisone. A computer search back to 1967 produced 72 additional cases of esophageal CD. Among these 75 patients (total), who were, on average, 34 years old, esophageal disease was the presenting disease symptom in 41 patients (55%). The diagnosis was difficult in 13 patients, in whom no distal bowel disease was detected at the time of initial esophageal presentation. The most common presentation was dysphagia associated with aphthous or deeper ulcerations (52 patients). In 11 of these patients, oral aphthous ulcerations were also present. Esophageal stenosis or fistulas to surrounding structures were present in 27 patients and led to surgery in 17 patients. Most of the unfavourable outcomes were in this group of 27 patients with esophageal complications, including five deaths. Fourteen additional patients required surgery for CD of other areas. Responses of uncomplicated ulcerative disease of the esophagus tended to be favourable if the medical regimen included prednisone. Clinical patterns of esophageal CD were divided into three categories: ulcerative, stenosing and asymptomatic (acute disease in children).